Analysis of Collection Micro, Small and Medium-Sized Enterprises (MSMEs) Receivable on Bank BJB KCP X Customers - Oktaviani, Rima; Sutarsa, Monika (PT. Riset Press International, 2024)
Receivables are a crucial aspect in the financial industry. Effective handling is the key to the sustainability of bank operations. This research analyzes the procedures for collecting MSME receivables from Bank BJB KCP X customers. This research uses descriptive qualitative methods with data collection techniques through interviews, observation and literature study. The research results show that the receivables collection procedure at Bank BJB KCP collection. Based on the research results, several solutions are recommended to increase the effectiveness of receivables collection, including strengthening education for customers regarding receivables collection procedures, increasing coordination with related parties in the receivables collection process, utilizing digital technology to simplify the receivables collection process. It is hoped that this research will provide benefits for Bank BJB KCP.